SENSITIVITY OF ANTIBIOTIC IN DIABETIC ULCER BACTERIA AND ITS MANAGEMENT IN INDONESIA. A LITERATURE REVIEW - Umi Margi Rahayu; Anis Laela Megasari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Introduction: Diabetic ulcer is one of the complications of Diabetes Mellitus (DM) which is characterized by an open wound on the skin layer up into the dermis. One of the inhibitors of wound healing process is infection. The bacteria that present in the ulcer are a combination of aerobic and anaerobic bacteria. Treatment of infection is closely related to the use of antibiotics. Methods: The method used in this paper is literature review and was conducted from 2010 – 2016. The research articles were reviewed from electronic databases including Science Direct, CINAHL, Pub Med, Pro Quest, and from relevant textbooks. The keywords used include diabetic ulcer, antibiotic, management ulcer, and wound care. Results: The entry of bacteria into the early occurrence of diabetic ulcers and high glucose levels become trategic places of bacterial development. The most common types of bacteria found in diabetic ulcers, Staphylococcus sp, Streptococcus sp, Pseudomonas sp, and E.Coli, are still sensitive to antibiotic class of balaktam (Imepenam and Meropenam) whereas antibiotics that are resistant to these bacteria are amoxicillin and penicillin. Provision of antibiotic therapy should still be combined with wound care with a dressing that has antimicrobial properties, given the many types of bacteria found in diabetic ulcers with different types and sensitivity patterns to antibiotics. Conclusions: Many cases in diabetic ulcer are infection and many types of bacteria are resistant to antibiotic. Prevention of resistance can be done with the selection of specific antibiotics, the combination of aerobic and anaerobic antibiotics, and the regularity of antibiotics including the timeliness and dose. Management of diabetic ulcers should be carried out comprehensively, not just focusing on antibiotics, but also with wound care, given the many types of bacteria found in diabetic ulcers with different types and sensitivity patterns to antibiotics.